Development of a PCM-HE to harness waste greywater heat: A case study of a residential building. (1st February 2022) - Mazhar, Abdur Rehman; Zou, Yuliang; Liu, Shuli; Shen, Yongliang; Shukla, Ashish
Highlights: A three-step methodology to develop a HE for harnessing GW heat is put forward. A PCM-HE with finned-corrugated pipes can be developed for versatile applications. A technique simulating a unit volume determines performance of the holistic PCM-HE. A developed PCM-HE saves 20–40% heat in residential buildings, as per a case study. This novel methodology and technique can be applied in numerous energy applications. Abstract: Waste greywater (GW) from non-industrial buildings has considerable exergy that must be exploited for a sustainable future. Scavenging this low-grade heat from GW into cold water (CW) before storage in a phase change material (PCM) is a novel approach to decouple demand and supply along with integrating storage and transfer in a single heat exchanger (HE). A methodology to optimally select an appropriate PCM along with the heat transfer enhancement procedures both internal and external to the flow pipes is presented. This procedure can be extended to reduce the hot water heating demand for applications in both residential and larger commercial buildings. Furthermore, a design technique to numerically assess the performance of a full-scale HE based on empirical formulations of a unit-volume are also put forward. As a case study, the performance of a counter-flow PCM-HE with vertically cascaded GW and CW finned-corrugated pipes is assessed for heat recovery in household appliances of a residential building. Such HE with 9 m piping length can increment the incoming CW temperature by 9.5 K with complete phase change of 30 kg of PCM in 900 s. A transfer of about 5, 100 kJ of heat for PCM melting with GW outflow and freezing with CW inflow occurs within this time frame. Furthermore, to fully exploit the temperature differences between the fluids a three-cascaded PCM arrangement enhances the CW outlet temperature by 64%. The installation of this PCM-HE in a four-member UK household, can save 4, 687 kWh of energy annually with a payback time of 4.44 years.